Factor analysis of Self-reliance in health according to the philosophy of sufficiency economy among the older adults outside municipal areas Phetchaburi Province - Rujiganjanarat, Kitisak; Durongritichai, Vanida (Journal of Medical and Public Health Region 4, 2025)
This descriptive research aims to analyze the confirmatory factors of health self-reliance in accordance with the Sufficiency Economy Philosophy. Data were collected from older adults residing outside the municipality area of 17 sub-districts in Phetchaburi Province, totaling 310 individuals, using cluster sampling. The instrument used was a questionnaire employing a 5-level rating scale with 24 items. Content validity was assessed by determining the consistency index value, which was found to be 0.97. Reliability testing using Cronbach's alpha coefficient yielded a value of 0.94. Data were analyzed using descriptive statistics and confirmatory factor analysis. The results of the study indicated that the examination of the consistency of the components of health self-reliance according to the Sufficiency Economy Philosophy yielded Chi-square = 5.87, df = 5, χ2/df = 1.174, p = 0.319, CFI = 0.997, TLI = 0.994, SRMR = 0.015, and RMSEA = 0.024. These values suggest that the model of health self-reliance components based on the Sufficiency Economy Philosophy is consistent with the collected data. Divided into 5 components: 1) psychological aspect, 2) social aspect, 3) natural resources and environment, 4) technology aspect, and 5) economic aspect, the component with the highest weight indicating self-reliance in health is the economic aspect, with a component weight value of 1.18. This value suggests that the economic aspect can indicate 87 percent of self-reliance in health according to the Sufficiency Economy Philosophy. Therefore, the findings of this study can serve as a guideline for assessing and developing suitable activities to enhance health self-reliance among older adults.